EVALUATION OF MARKETING MECHANISM IN FARM DEVELOPMENT - Nazarova Gulruh Umarjonovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article will explore key aspects such as developing an effective farm marketing mechanism, utilizing digital technologies and innovative marketing tools, segmenting the market, implementing pricing strategies and branding, and analyzing factors that contribute to the competitiveness of farms in the agricultural sector. The study also delves into practical methods and approaches necessary for successful marketing and enhancing the competitiveness of agricultural products in the market, including the production of environmentally friendly products and improving their quality.